Tales from the Edge: Narrative Voices in Information Research and Practice - Hodges, Kristin; Meyers, Eric; O'Brien, Heather (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2014)
Proceedings of the CAIS/ACSI 2013 conference.